Deseminasi Sistem Terintegrasi Budidaya Lobster dan Kerang Abalon di Desa Ekas Buana Kabupaten Lombok Timur - Muhammad Junaidi; Syawalina Fitria; Awan Dermawan; Muhammad Sumsanto (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Lobster and abalone cultivation with an integrated system is a technological innovation that has the potential for development, in addition to increasing business productivity with an integrated system capable of reducing environmental impacts and optimizing water quality to support the growth of cultivated commodities. Therefore, this integrated cultivation system needs to be disseminated to the farming community through various dissemination methods. Therefore, the purpose of this community service activity is to disseminate the integrated system of lobster and abalone cultivation to the community to address the productivity of the cultivation business through demonstration plots. The dissemination activity of the integrated system of lobster and abalone cultivation was carried out with the partners involved, namely the Pokdakan Pasir Putih Desa Ekas Buana. The activity stages include the stages of preparation of materials and tools, coordination and socialization, implementation of demplots, monitoring and evaluation. The results of this dissemination activity to the farming community are very effective through demonstration plot activities. The demonstration plot of lobster and abalone cultivation with an integrated system obtained a significant increase in the growth performance of lobster and abalone weight by 209% and 74%, respectively. The practice of an integrated lobster and abalone cultivation system is effective in overcoming the low productivity of floating net cage cultivation businesses, where farmers harvest two commodities, namely lobster and abalone.